(untitled) (Fiep Bulletin - online, 2012)
The article presents the different meanings of the term “adapted”, and the difference between“physical activity” and “adapted physical activity”.Adaptation is considered from three different angles: perspective of sports and sports logics,perspective of social view and activity’s internal logics, perspective of motor view and emotional andmotor-sensory pleasure. Handicapped people’s real demands, operating possibilities and interest willdetermine whether the sport, social or motor perspective is to be taken for their development.Since 1975 Italy has accomplished school level integration of all physically and mentallyhandicapped people (from the less to the most serious cases), whom represent 78.71% of totalintegrated students, as it can be seen from MPI (Public Education Ministry) data. For this reason theproblem of defining which kind of adaptation is needed for these kinds of students is particularly felt byresearchers and people operating in the sector and is a key issue particularly difficult to resolve.